Effect of Development of Patient Triage Guideline Based on the MOPH ED Triage Model for the Emergency Department of Mueang Songkhla Hospital - Jomtong, Aphinya; Binsama, Salisa (Princess of Naradhiwas University Journal, 2026)
Background and Objectives Developing clear and easy-to-understand patient triage guidelines is a crucial step in effectively reducing errors and increasing the accuracy of patient triage. Therefore, this research aimed to develop patient triage guideline based on the MOPH ED Triage model and evaluate its effectiveness in improving the quality of service in the emergency department of Songkhla Hospital. Methods This study was action research using a one-group pretest–posttest design. It was conducted in four phases: (1) Plan: Study the problem and situation before implementing the guideline from 20 medical personnel responsible for patient triage and 427 medical record officers; (2) Act: Develop the guideline and train personnel; (3) Observe: Evaluate the results after implementing the guideline from 20 personnel and 434 medical record officers. Data were analyzed using descriptive statistics and independent t-tests; (4) Reflect: Analyze the strengths, areas for improvement, and development directions of the guideline. Results The developed guideline improved the accuracy of patient triage from 79.40% to 88.70%. Additionally, the study found a significant reduction in waiting time for all patient groups at a level of 0.05. Regarding staff satisfaction, the guideline was highly rated, particularly in terms of accuracy, practicality, and benefits to patients and the department. Conclusion and Recommendations The study results can be used as a guideline for developing and improving patient triage guidelines in the emergency department and can effectively enhance the quality of medical services.